2005
DOI: 10.4315/0362-028x-68.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Bacillus circulans and Paenibacillus polymyxa Strains Inhibitory to Campylobacter jejuni and Characterization of Associated Bacteriocins

Abstract: We evaluated anti-Campylobacter activity among 365 Bacillus and Paenibacillus isolates from poultry production environments. One novel antagonistic Bacillus circulans and three Paenibacillus polymyxa strains were identified and further studied. Cell-free ammonium sulfate precipitate (crude antimicrobial preparation) was obtained from each candidate culture. Zones of Campylobacter growth inhibition surrounding 10 microl of this crude antimicrobial preparation were quantified using a spot test. Campylobacter gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
75
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 22 publications
(26 reference statements)
0
75
1
Order By: Relevance
“…In our experimental conditions, Paenibacillus sp. CWBI B1070 did not exert any anti-Campylobacter activity, in contrast to the results of Svetoch et al [33], who reported antagonistic activities against Campylobacter of one Bacillus and three Paenibacillus strains isolated from the poultry production environment.…”
Section: Discussioncontrasting
confidence: 56%
“…In our experimental conditions, Paenibacillus sp. CWBI B1070 did not exert any anti-Campylobacter activity, in contrast to the results of Svetoch et al [33], who reported antagonistic activities against Campylobacter of one Bacillus and three Paenibacillus strains isolated from the poultry production environment.…”
Section: Discussioncontrasting
confidence: 56%
“…polymyxa has also been isolated from several places such as food, rhizosphere, poultry production environments, and soils; and most of them can restrain fungal pathogen growth (He et al, 2007;Raza et al, 2009;Svetoch et al, 2005). Further studies will investigate the anti-fungal pathogen activity of the isolate EBL-06 both in phyllosphere and in rhizosphere by field trials.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with other culture media, the mixture of SPW and MGW is the most suitable for the biocontrol agent production from the economic and environmental point of view. P. polymyxa has also been isolated from several places such as food, rhizosphere, poultry production environments, soils and most of them can restrain fungal pathogen growth (He et al, 2007;Raza et al, 2009;Svetoch et al, 2005). Further studies will investigate the antifungal pathogen activity of the isolate EBL06 both in phyllosphere and in rhizosphere by field trials.…”
Section: Disscussionmentioning
confidence: 99%